The nociceptive response induced by different classes of Tityus serrulatus neurotoxins: The important role of Ts5 in venom-induced nociception. - Felipe Cerni; Isadora Oliveira; Francielle Cordeiro; Karla Bordon; Isabela Ferreira; Wuelton Monteiro; Eliane Arantes; Thiago Cunha; Manuela Pucca (PLoS Neglected Tropical Diseases, 2023)
Scorpion sting envenomations (SSE) are feared by the intense pain that they produce in victims. Pain from SSE is triggered mainly by the presence of neurotoxins in the scorpion venom that modulates voltage-gated ion channels. In Brazil, SSE is mostly caused by Tityus serrulatus, popularly known as yellow scorpion. Here, we evaluated experimental spontaneous nociception induced by T. serrulatus venom as well as its isolated neurotoxins Ts1, Ts5, Ts6, Ts8, and Ts19 frag II, evidencing different degrees of pain behavior in mice. In addition, we developed a mice-derived polyclonal antibody targeting Ts5 able to neutralize the effect of this neurotoxin, showing that Ts5 presents epitopes capable of activating the immune response, which decreased considerably the nociception produced by the whole venom. This is the pioneer study to explore nociception using different classes of T. serrulatus neurotoxins on nociception (α-NaTx, β-NaTx, α-KTx, and β-KTx), targeting potassium and sodium voltage-gated channels, besides demonstrating that Ts5 plays an important role in the scorpion sting induced-pain.